Motion Estimation Techniques for Digital Video Coding - Metkar, Shilpa; Talbar, Sanjay; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
The book deals with the development of a methodology to estimate the motion field between two frames for video coding applications. This book proposes an exhaustive study of the motion estimation process in the framework of a general video coder. The conceptual explanations are discussed in a simple language and with the use of suitable figures. The book will serve as a guide for new researchers working in the field of motion estimation techniques.
Introduction -- Performance Evaluation of Block Matching Algorithms for Video Coding -- Fast Motion Estimation using Modified Orthogonal Search Algorithm for Video Compression -- Dynamic Motion Detection Techniques -- Conclusion and Research Directions -- Bibliography.
Keywords: Engineering; Computer graphics; Computational intelligence; Engineering; Computational Intelligence; Signal, Image and Speech Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books